Analisis Permintaan dan Penawaran Ternak Sapi di Nusa Tenggara Barat - Soekardono Soekardono; Lalu Muhammad Kasip; muhammad nur (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2015)
The research aims to describe the technical coefficient of cattle population and production and to determine the relationship among technical parameters that affect population dynamics as well as supply and demand of cattle in West Nusa Tenggara. This research was analyzed the secondary data which published by Veterinary and Livestock Office West Nusa Tenggara Province during 2010-2014. The potential of breeds has increased on average 14.09 % of 102.342 heads in 2010 to 173.092 heads in 2014 while the realization of export has reached average 36.50 % in the last five years as well as the potential of cattle increased by 15.26 % from 76.050 in 2010 to 133.260 in 2014. At the same periods, the realization of cattle export has reached 45.67 % from targets which have been set. It was estimated that population growth rate at the end this period increased by 13.84 %. Meanwhile, the population growth derived from annual livestock updating is 10.02 %. To further enhance development of cattle, the government should : increase the economic value of cattle farming mainly in rural areas, promote partnerships with state-owned enterprises (BUMN), provide incentives for farmers by local regulation for breeding and fattening in order to provide added value while improve farmer’s welfare.